Student motives, expectations and preparedness for higher education: A gender-based study (Journal of Student Affairs in Africa, 2024)
This study aimed to identify whether gender differences exist related to the motives, expectations and preparedness of students entering accounting studies at a South African university. A questionnaire was used to gather the data from a sample of first-year students and t-tests were employed to identify differences in findings between gender groups. The findings indicate that gender differences exist in the motives for studying and for choosing to study accounting, in particular with females indicating a stronger desire to gain a better understanding of themselves, while males appeared more confident of succeeding in the programme and scoring marks at the top of the class. Identifying and understanding gender differences is expected to have implications for teaching and learning which can further reduce gender imbalances in the profession. The study is of particular interest to academics, professional bodies and universities educating students in the field of accounting, which has historically been perceived to be a male-dominated profession.